Potential Driven Volume Diffusion in Nanoporous AgBi at Room Temperature. (6th January 2023) - Zhou, Xiangji; Qian, Lihua; Yu, Tianshui; Xiao, Hengbo; Liu, Lin; Yu, Yao; Lei, Pengxiang
Abstract: Volume diffusion is crucial for crystal growth and interface manipulation in electron devices and catalysts. Its kinetics only becomes vigorous at high temperature, in which case grain boundary diffusion and surface diffusion dominate usually. In this study, volume diffusion of Bi atoms in nanoporous AgBi can be driven by electrochemical potential at room temperature due to ligament expansion. Bi diffusion induces conformal covering of amorphous Bi2 O3 shell onto the spatially interconnected skeletons without ligament coarsening. Growth kinetics of amorphous shell demonstrates that the potential dependence of Bi volume diffusion activation energy corresponds to 0.932 eV V −1 . Compared with temperature dependence, potential supply is confirmed to be more feasible to modulate volume diffusion rate and shell thickness, and Bi enrichment increases 3.4 times when potential raises from −0.85 to −1.05 V. Potential driven volume diffusion at room temperature reported here knobs one door to manipulate local composition of functional nanostructures and nano‐devices at atomic scale. Abstract : A conformal amorphous Bi2 O3 shell is formed on the ligaments of nanoporous AgBi by Bi volume diffusion driven by electrochemical potential. Experimental analysis of the diffusion kinetic shows the advantage to controlling the growth rate and thickness of amorphous shell by adjusting potential.